Dynamic cerebral perfusion parameters and magnetic nanoparticle accumulation assessed by AC biosusceptometry - Próspero, André Gonçalves [UNESP]; Soares, Guilherme Augusto [UNESP]; Moretto, Gustavo Morlin [UNESP]; Quini, Caio C. [UNESP]; Bakuzis, Andris Figueiroa; De Arruda Miranda, José Ricardo [UNESP] (De Gruyter, 2020)
Cerebral blood flow (CBF) assessment is mainly performed by scintigraphy, computed tomography (CT) and magnetic resonance imaging (MRI). New approaches to assess the CBF through the passage of magnetic nanoparticles (MNPs) to blood-brain barrier (BBB) are convenient to help decrease the use of ionizing radiation and unleash the required MRI schedule in clinics. The development of nanomedicine and new biomedical devices, such as the magnetic particle imaging (MPI), enabled new approaches to study dynamic brain blood flow. In this paper, we employed MNPs and the alternating current biosusceptometry (ACB) to study the brain perfusion. We utilized the mannitol, before the MNPs, injection to modulate the BBB permeability and study its effects on the circulation time of the MNPs in the brain of rats. Also, we characterized a new ACB sensor to increase the systems' applicability to study the MNPs' accumulation, especially in the animals' brain. Our data showed that the injection of mannitol increased the circulation time of MNPs in the brain. Also, the mannitol increased the accumulation of MNPs in the brain. This paper suggests the use of the ACB as a tool to study brain perfusion and accumulation of MNPs in studies of new nano agents focused on the brain diagnostics and treatment.
Keywords: AC biosusceptometry; biodistribution; cerebral perfusion; magnetic nanoparticles; mannitol